2014
DOI: 10.1080/15434303.2013.872647
|View full text |Cite
|
Sign up to set email alerts
|

Corpora and Language Assessment: The State of the Art

Abstract: This article outlines the current state of and recent developments in the use of corpora for language assessment and considers future directions with a special focus on computational methodology. Because corpora began to make inroads into language assessment in the 1990s, test developers have increasingly used them as a reference resource to become well versed in terms of the linguistic characteristics of expert and novice speakers' usage and identify the test construct. In regard to developing and validating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 71 publications
(75 reference statements)
2
8
0
1
Order By: Relevance
“…This study has shown that for the analysis of learner language, even small longitudinal corpora can be useful for the derivation of 'successful' student texts if performance is measured against a set of criterion used for the assessment of such success. Here, though, we agree with Park (2014) in claiming that existing criterial features used for the assessment of student performance may be unreliable "until a robust statistical relationship between given identified features and the learner's linguistic competence has been established" (p. 39). We believe our findings have made such a relationship clear.…”
Section: Resultssupporting
confidence: 69%
“…This study has shown that for the analysis of learner language, even small longitudinal corpora can be useful for the derivation of 'successful' student texts if performance is measured against a set of criterion used for the assessment of such success. Here, though, we agree with Park (2014) in claiming that existing criterial features used for the assessment of student performance may be unreliable "until a robust statistical relationship between given identified features and the learner's linguistic competence has been established" (p. 39). We believe our findings have made such a relationship clear.…”
Section: Resultssupporting
confidence: 69%
“…The findings showed that high-scoring essays contained more creative academic formulae, while low scoring essays included multiword units taken from the source material. Their findings support using small corpora to reveal the differences in test-takersp roficiency as measured by the use of multiword units (Park, 2014).…”
supporting
confidence: 54%
“…Their findings support using small corpora to reveal the differences in test-takersp roficiency as measured by the use of multiword units (Park, 2014). Adapting an interactional and sociolinguistic perspective, the author reports on validity evidence for a web-based test of pragmatics that includes multiturn discourse completion tasks as well as appropriateness judgments and single-turn items.…”
mentioning
confidence: 69%
“…However, recently there has been an increasing awareness of some crucial aspects at the interface of the fields, along with a growing readiness to integrate insights from all these areas into proficiency level–related research. This has led to much broader research perspectives (LTA and SLA: Alderson, ; Hulstijn et al., ; Leclercq, Edmonds, & Hilton, ; LTA and LCR: Barker, ; Barker et al., ; Callies et al., ; Callies & Götz, ; Callies & Paquot, ; Park, ; Taylor & Barker, ; LCR & SLA: Hasko & Meunier, ; Myles, ).…”
Section: Opportunities and Challenges Of Working Across Disciplinary mentioning
confidence: 99%